Endovascular repair of acute complicated type B aortic dissection—systematic review and meta-analysis of long-term survival and reintervention - Wilson-Smith, Ashley R.; Muston, Benjamin; Kamalanathan, Harish; Yung, Amanda; Chen, Cheng-Hao Jacky; Sahai, Prachi; Eranki, Aditya (Annals of Cardiothoracic Surgery, 2021)
Background: Thoracic endovascular repair (TEVAR) is considered the first-line therapy in the repair of acute complicated type B aortic dissection (AC-BAD). Given the difficulty of designing randomized trials in this surgical cohort, long-term outcome data is limited. This systematic review and meta-analysis provide a complete aggregation of reported long-term survival and freedom from reintervention of AC-BAD patients based on the existing literature. Methods::